2016
DOI: 10.1098/rspb.2016.1184
|View full text |Cite
|
Sign up to set email alerts
|

Parallel telomere shortening in multiple body tissues owing to malaria infection

Abstract: Several studies have shown associations between shorter telomere length in blood and weakened immune function, susceptibility to infections, and increased risk of morbidity and mortality. Recently, we have shown that malaria accelerates telomere attrition in blood cells and shortens lifespan in birds. However, the impact of infections on telomere attrition in different body tissues within an individual is unknown. Here, we tested whether malarial infection leads to parallel telomere shortening in blood and tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 38 publications
(57 reference statements)
2
51
2
1
Order By: Relevance
“…In comparison, smoking is thought to cause an estimated 3 bp/year steeper decline in BTL with age (Benetos et al, 2013). Recent evidence from experimental infection of a bird with avian malaria showed TL shortening in not just blood, but also liver, lung, spleen, heart, kidney and brain (Asghar et al, 2016). BTL is a marker of the TL of hematopoietic stem cells and shorter hematopoietic stem cell TL could have important effects on leukocyte and erythrocyte production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, smoking is thought to cause an estimated 3 bp/year steeper decline in BTL with age (Benetos et al, 2013). Recent evidence from experimental infection of a bird with avian malaria showed TL shortening in not just blood, but also liver, lung, spleen, heart, kidney and brain (Asghar et al, 2016). BTL is a marker of the TL of hematopoietic stem cells and shorter hematopoietic stem cell TL could have important effects on leukocyte and erythrocyte production.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, and birds experimental infections have been shown to cause shortened TLs (Ilmonen et al, 2008; Asghar et al, 2015; Asghar et al, 2016). In humans, studies examining associations between infectious diseases and blood or lymphocyte TL have primarily been limited to adults in clinical contexts from high income countries.…”
Section: Introductionmentioning
confidence: 99%
“…and the chicken(Li et al, 2014). Furthermore, since blood has been shown to reflect changes occurring in other tissues(Asghar et al, 2016;Watson, Videvall, Andersson, & Isaksson, 2017), the observed changes might not only suggest a wide window of sensitivity to environmentally induced epigenetic changes for this particular tissue, but at the whole-organism level. The occurrence of genome-wide changes in methylation in blood throughout postnatal development is of foremost ecological relevance, as it suggests a wide window during which environmentally induced epigenetic modifications could occur.…”
mentioning
confidence: 92%
“…Both Plasmodium infection alone and infection intensity (i.e. parasitaemia) of Plasmodium have been previously associated with increased oxidative damage to plasma metabolites and to DNA [2, 34, 35]. Taken together, these results show that the oxidative stress phenomenon and its interplay with infection are complex and therefore need to be studied using a range of markers that capture different aspects of the oxidative process.
Fig.
…”
Section: Introductionmentioning
confidence: 73%
“…The higher pro-oxidant release by mitochondria in infected individuals suggests that Plasmodium parasites impose a cost on their host in terms of an enhanced energy requirement resulting in increased oxidative stress. This may have further important consequences in terms of oxidative damage leading to telomere shortening in red blood cells [2] but also in other tissues [35] potentially triggering a faster ageing associated with malaria disease.…”
Section: Resultsmentioning
confidence: 99%